2015
DOI: 10.1016/j.jjcc.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Combination of pulse wave velocity with clinical factors as a promising tool to predict major adverse cardiac events after percutaneous coronary intervention

Abstract: Combination of PWV with age, creatinine clearance, and left ventricular ejection fraction appears to be a promising tool to predict MACE after PCI in patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…26 In patients with pre-existing CAD, PWV was also reported to be significantly associated with incidence of MACE. 27 In a similar population, Weber et al also reported that the AIX was significantly associated with incidence of MACE. 28 The results of these studies are consistent with a recent meta-analysis of prospective studies assessing the relationship between PWV and incidence of cardiovascular disease, CAD, and stroke.…”
Section: Discussionmentioning
confidence: 90%
“…26 In patients with pre-existing CAD, PWV was also reported to be significantly associated with incidence of MACE. 27 In a similar population, Weber et al also reported that the AIX was significantly associated with incidence of MACE. 28 The results of these studies are consistent with a recent meta-analysis of prospective studies assessing the relationship between PWV and incidence of cardiovascular disease, CAD, and stroke.…”
Section: Discussionmentioning
confidence: 90%
“…Knowledge about the association between CFPWV and the result of commonly used CVD risk assessment systems such as the SCORE system is still limited [22][23][24]. Because most European countries use different SCORE charts, it is particularly important to assess its results with other measurements.…”
Section: Discussionmentioning
confidence: 99%
“…LVEF may be maintained by enhanced torsion despite reduced myocardial shortening [17][18][19]. This could explain why lower AAD rather than relatively maintained LVEF can better predict adverse events, even though LVEF is known to be an important index to predict cardiac events [20].…”
Section: Prognostic Value Of Aadmentioning
confidence: 99%